2016
DOI: 10.1007/s10865-016-9772-4
|View full text |Cite
|
Sign up to set email alerts
|

Managing severe obesity: understanding and improving treatment adherence in bariatric surgery

Abstract: Severe obesity (body mass index ≥40 kg/m) is a chronic disease that is associated with significantly increased risk of serious and chronic health problems as well as impaired quality of life. For those with severe obesity, bariatric surgery is the most effective treatment for significant and long-term weight loss and resolution of comorbid medical conditions, particularly diabetes. Long-term success is thought to depend to some degree on the patient's ability to adhere to a complex set of behaviors, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 87 publications
6
52
0
2
Order By: Relevance
“…They emphasised that if the patient did not change certain behaviours, it would lead to maladaptive consequences, such as vomiting and stomach acid reflux. Unfortunately, patients often underestimate the expected physiological changes and restrictions, especially when the body weight quickly decreases within 1 year after surgery(Hood et al, 2016). When making mistakes with respect to their eating behaviour or other behaviours, the body immediately experienced physical dis-Characteristics of the participants To control caloric intake after surgery and follow restrictions related to having a small stomach, the consumption of foods that can easily occupy gastric capacity must be reduced.…”
mentioning
confidence: 99%
“…They emphasised that if the patient did not change certain behaviours, it would lead to maladaptive consequences, such as vomiting and stomach acid reflux. Unfortunately, patients often underestimate the expected physiological changes and restrictions, especially when the body weight quickly decreases within 1 year after surgery(Hood et al, 2016). When making mistakes with respect to their eating behaviour or other behaviours, the body immediately experienced physical dis-Characteristics of the participants To control caloric intake after surgery and follow restrictions related to having a small stomach, the consumption of foods that can easily occupy gastric capacity must be reduced.…”
mentioning
confidence: 99%
“…General nutritional guidelines post-surgery prioritize protein intake, minimizing high carbohydrate and high fat foods, eliminating caloric beverages, and increasing the consumption of fruits and vegetables. [17] Fruits and vegetables provide the body with a wide range of nutrients. [18] In our study, the average intake of fruits and vegetables were "once daily" 1.51 ± 0.79, and 1.78 ± 0.76, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of control over eating is a proxy for binge eating, as post-bariatric patients cannot consume large quantities of food in one sitting. [17] Saunders observed that many patients report feelings of loss of control over eating after bariatric surgery and, in some cases, weight gain after several years. [23] Changing the mindset over binge eating is quite tough and challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges involved in post-bariatric surgery follow up have been associated with several factors (20), such as younger age (9,(21)(22)(23), unemployment or retired employment status (22), and lack of insurance coverage (9,13). Additional psychological risk factors include the presence of symptoms of attention deficit hyperactivity disorder (24), avoidant attachment (relationship) style (25), depression (12), narcissistic personality traits (26), phobic anxiety (27) and impulsivity (28).…”
Section: Introductionmentioning
confidence: 99%